A Commentary on Song of Moses in the Exodus 15:1-7 (LXX-Rahlfs) - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
Studying the books in the Old Testament which were originally in Hebrew, then studied through the Greek edition with the Septuagint will broaden horizons in Biblical studies. There are various editions of the Septuagint. In this study, it will use Rahlfs' edition. This edition is the most widely spread edition of the Septuagint. Alfred Rahlfs edition of the Septuagint (Rahlfs Septuagint), is a critical edition of the Septuagint published for the first time in 1935 by the German philologist. Through this paper, a structured study of the text of Exodus 15:1-7 will be presented.